ANESTEZJOLOGIA I INTENSYWNA TERAPIADonor management – the role of not only anesthetist - Saucha, Wojciech; Maruszewski, Marcin; Kucewicz-Czech, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The identification of potential donors of organs in Poland still encounters many problems. Ill at which one can suspect the brain death are often treated outside structures of Intensive care units. The declaration of the brain death and the bringing to organ harvesting requires the execution of the strictly determined procedures but also some extra-medical skills first of all the endurance and the determination. Currently in Poland are employed hospital transplantation coordinators. What should be their role? Who can become a coordinator?